2001
DOI: 10.1007/s00438-001-0589-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus nidulans DigA, a potential homolog of Saccharomyces cerevisiae Pep3 (Vps18), is required for nuclear migration, mitochondrial morphology and polarized growth

Abstract: The fungal vacuole is an acidic organelle that is involved in a variety of physiological processes, such as protein turnover, ion and pH homeostasis and osmoregulation. The function of the vacuole largely depends on vesicle transport providing the organelle with enzymes and substrates. The process of vesicle transportation has been studied best in Saccharomyces cerevisiae, where several proteins that are crucial for intracellular vesicle sorting have been identified. One such protein is Pep3 (Vps18). In pep3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…dscE was selected for preliminary analysis in A. fumigatus since it has not been previously studied in the filamentous fungi. One strain contained a deletion in a gene encoding a homolog of Aspergillus nidulans DigA, which is involved in nuclear migration, mitochondrial morphology, and polarized growth (25). However, it is an essential gene in N. crassa that can survive only as a heterokaryon, and we were unable to generate digA deletion strains in A. fumigatus (data not shown).…”
Section: Identification Of Novel Hypoxia-sensitive Mutants In N Crassamentioning
confidence: 96%
“…dscE was selected for preliminary analysis in A. fumigatus since it has not been previously studied in the filamentous fungi. One strain contained a deletion in a gene encoding a homolog of Aspergillus nidulans DigA, which is involved in nuclear migration, mitochondrial morphology, and polarized growth (25). However, it is an essential gene in N. crassa that can survive only as a heterokaryon, and we were unable to generate digA deletion strains in A. fumigatus (data not shown).…”
Section: Identification Of Novel Hypoxia-sensitive Mutants In N Crassamentioning
confidence: 96%
“…Therefore, at least some VPS proteins are presumed to be involved in hyphal morphogenesis in A. oryzae. In A. nidulans, a mutation in digA, a potential homolog of S. cerevisiae VPS18/ PEP3, results in dichotomous and subapical branches (8), which also suggests a correlation between vacuolar protein sorting and hyphal morphogenesis. The properties of multicellularity and cell polarity specific to filamentous fungi may provide an opportunity to characterize morphological abnormalities that cannot occur in unicellular microorganisms such as S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one cycloheximide-sensitive mutant of A. nidulans shows fragmentation of vacuoles (6). Geissenhoner et al (8) showed that mutation of digA, a homolog of the S. cerevisiae VPS18/PEP3 locus, causes fragmented vacuoles and clustered mitochondria and nuclei, suggesting that the protein functions in organellar positioning and cell polarity in A. nidulans. Previously, we isolated the vpsA, avaA, and avaB genes (homologs of S. cerevisiae VPS1, VAM4/YPT7, and VAM6/VPS39, respectively) from A. nidulans and demonstrated that these genes are involved in vacuolar biogenesis (15,17,26).…”
mentioning
confidence: 99%
“…Moreover, deletion of so-called class E VPS genes that are required for late endosome function and transport to vacuoles results in defective vacuole formation and growth in A. oryzae (Tatsumi et al 2006;Tatsumi et al, in preparation), while it does not affect either of them in the budding yeast (Raymond et al 1992). Apparently, vacuole formation is a prerequisite for proper growth and development in filamentous fungi, because mutations affecting vacuolar function result in defective hyphal growth and conidiation (Geißenhöner et al 2001;Palmer et al 2003;Veses et al 2005;Tatsumi et al 2006). The vital roles of vacuoles may make it difficult to obtain mutants which mis-secrete vacuolar proteins in filamentous fungi.…”
Section: Vacuolesmentioning
confidence: 95%